KEPEMIMPINAN ROHANI DAN RASULI DALAM PERSPEKTIF IGNATIAN - Sardi, Leo Agung (Jurnal Orientasi Baru, 2017)
Adolfo Nicolás, former superior general of the Society of Jesus, presented his elaboration on Ignatian leadership before the superiors and the directors of works in Valladolid, Spain in May 6, 2013. In his narrative style he focused on three characters of Ignatian leadership: spiritual, apostolic and heroic. It is spiritual, because Ignatian leadership works on the base of discernment both personal and communal. It is apostolic because the integrity of Ignatian leadership consists in its function to serve. Service is the final and most basic criteria to evaluate Ignatian leardeship. With regard to the third character Adolfo Nicolás elaborated heroic leadership reffering to Ignatian spirit of magis, choosing and doing more for the service and glory of God as well as for the common good of people. Heeding a tendency of being resistant to criticism from within the Church and without, he pointed to a habit of reflection as a crucial point in Ignatian leadership. It is indeed a prayerful aspect of leadership that protects leadership from becoming a mere management of power. He also mentioned preferential option for the poor as one constitutive point in the Jesuit life that should mark an Ignatian leadership.